There Is More to Being a Scotsman than Putting on a Kilt and Trilling your /r/s. A Study of Linguistic Credibility in the Hollywood Movie Braveheart - Pedersen, Jan (Miscelánea: A Journal of English and American Studies, 2007)
This article investigates the linguistic credibility of the Hollywood movie Braveheart (1995). After first discussing the producers’ choice of rejecting the reality of historically correct language use, in favour of transposing modern day socioliguistic realities, a phonetic analysis of the leading actor’s (Mel Gibson’s) attempts at a Standard Scottish English accent (SSE) is carried out. The analysis is mainly carried out at a phonemc level, where some stereotypically Scottish consonants and vowel sounds are analyzed. However, the focus of the analysis is on how well the actor has managed to imitate the Scottish Vowel Length Rule (or Aitken’s law). The result of the analysis is that Gibson has made quite an effort at Scotsman by a native SSE speaker, his efforts would probably be enough for the American (and international) viewers who are the primary audience of the film. It could be said that Mel Gibson is aiming for a more nuanced accent than just a farcical stereotype of SSE. Mel Gibson must have found that there is more to being a Scotsman than putting on a kilt and trilling your /r/s.
Keywords: Standard Scottish English; Scottish Vowel Length Rule (SVLR); linguistic credibility; film studies; dialect coaching